The Use of Next-Generation Sequencing for the Quality Control of Live-Attenuated Polio Vaccines. (3rd June 2020) - Charlton, Bethany; Hockley, Jason; Laassri, Majid; Wilton, Thomas; Crawt, Laura; Preston, Mark; ,; Rigsby, Peter; Chumakov, Konstantin; Martin, Javier
Abstract: Background: Next-generation sequencing (NGS) analysis was compared to the current MAPREC (mutational analysis by polymerase chain reaction and restriction enzyme cleavage) assay for quality control of live-attenuated oral polio vaccine (OPV). Methods: MAPREC measures reversion of the main OPV attenuating mutations such as uracil (U) to cytosine (C) at nucleotide 472 in the 5′ noncoding region of type 3 OPV. Eleven type 3 OPV samples were analyzed by 8 laboratories using their in-house NGS method. Results: Intraassay, intralaboratory, and interlaboratory variability of NGS 472-C estimates across samples and laboratories were very low, leading to excellent agreement between laboratories. A high degree of correlation between %472-C results by MAPREC and NGS was observed in all laboratories (Pearson correlation coefficient r = 0.996). NGS estimates of sequences at nucleotide 2493 with known polymorphism among type 3 OPV lots also produced low assay variability and excellent between-laboratory agreement. Conclusions: The high consistency of NGS data demonstrates that NGS analysis can be used as high-resolution test alternative to MAPREC, producing whole-genome profiles to evaluate OPV production consistency, possibly eliminating the need for tests in animals. This would be very beneficial for the quality assessment of next-generation polio vaccines and, eventually, for other live-attenuated viral vaccines. Abstract : A high degree of correlation between standard MAPREC test and NGS measurements of 472C nucleotide content in Sabin 3 oral polio vaccines was observed demonstrating that NGS can be used for the batch release of such vaccines.